Mulher Karajá: desvendando tradições e tecendo inovações - diálogo sobre as demandas de gênero - Torres, Maristela Sousa (2011)
Among the Karajá Indians, traditionally, women assume an important position in the social life despite the interdictions to which they are subjected in daily life, such as: not being allowed to enter the Aruanãs house, a place totally reserved for the men; not being allowed to walk along paths and spaces restricted to the male rituals and linked to the spirits, among others. With all these interdictions it seems that the women have a secondary role. However, when the socio-cultural dynamics of this people is understood, it is noticed that the women have a very comfortable life and gain social prestige as they get older, and this fact is directly associated with the context of the uxorilocal household. However, this social position of the Karajá woman, as well as her own life, is increasingly threatened due to the contact with the national society. This study is an attempt to identify the changes that are occurring, as well as to delineate a more comprehensive analysis of the factors that contribute to such changes, that guide the gender relations and that are directly associated to the threat of these women s lives, due to the context of the interethnic relationships